From Pattern to Product: An Analysis of the Relationship Between Learning Outcomes in Fashion Pattern Engineering and Women’s Fashion Production - Citra Hapsari; Wulansari Prasetyaningtyas (Jurnal Penelitian Pendidikan, 2026)
Mastery of fashion pattern engineering competencies is a fundamental requirement for success in applied fashion production learning. This study aims to examine the relationship between learning outcomes in the Fashion Pattern Engineering course and the Women’s Fashion Production course among students of the Fashion Education Study Program at Universitas Negeri Semarang, class of 2024. A quantitative ex post facto design was employed, involving 85 students selected through saturated sampling. Data were obtained from official academic records and analyzed using descriptive and inferential statistics, including the Shapiro–Wilk test, Levene’s test, and Spearman rank correlation. The results indicated that the data were not normally distributed but homogeneous. A positive and significant correlation was found (r = 0.447; p < 0.001), categorized as moderate. These findings suggest that pattern engineering competence contributes to student achievement in fashion production. Therefore, strengthening instructional integration and supporting learning factors is necessary to improve learning outcomes.